Proposição para cultivo hidropônico em movimento para alface Brunela - Estevam, Camila Genaro [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Lettuce (Lactuca sativa L.) is the most economically important leafy vegetable in Brazil and its cultivation in hydroponic systems has been increasing each year. Therefore, there is a growing search of technologies aimed at better adaptation to the Brazilian climate as biotechnology research to develop new cultivars and hybrids and the development of management techniques to produce on a comercial scale. The interception of light is the primary process for photosynthesis, carbon balance and plant growth. However, the light interception and the use of light energy by the plant are limited by the physiology of the photosynthetic metabolism of lettuce plants. In this context, this paper proposes to present existing methods on the market aimed at increasing the luminous efficiency and increased productivity. We also propose a new adaptation to the Nutrient Film Technique hydroponic system. It consists in changing the linear arrangement of the growing tubes for a circular and rotational arrangement of tubes, rouding a central axis in order to produce more plants per unit area and improve the efficiency of light capture

A alface (Lactuca sativa L.) é a hortaliça folhosa de maior importância econômica no Brasil e a utilização de cultivo em sistema hidropônico vem aumentando cada vez mais. Logo, há uma crescente busca pelo aprimoramento, tanto do sistema quanto dos cultivares e híbridos e de técnicas de manejo, visando a maior adaptação ao clima brasileiro. A interceptação de luz é o processo primordial para a fotossíntese, balanço de carbono e crescimento da planta. Contudo, a interceptação de luz e a utilização da energia luminosa pela planta estão limitadas pela fisiologia do metabolismo fotossintético de plantas de alface. Diante desse contexto, o presente trabalho propõe apresentar métodos já existentes no mercado que visem ao aumento da eficiência luminosa e aumento da produtividade. Também propomos uma nova adaptação ao sistema hidropônico, do tipo Nutrient Film Technique (NFT), alterando a disposição linear dos tubos desse sistema, para tubos dispostos circularmente a um eixo central e em movimento para justamente melhorar a eficiência de uso da luz
Keywords: Plantas - Nutrição; Olericultura; Luz; Hidroponia; Alface; Plantas